2021
DOI: 10.1007/s12144-021-01701-y
|View full text |Cite
|
Sign up to set email alerts
|

The 5-factor model of psychological response to COVID-19: its correlation with anxiety and depression

Abstract: The present study aimed to investigate the psychological response to COVID-19 on a community Egyptian sample and the correlation thereof with anxiety and depression. Further, we aimed to explore the differences in the psychological response and psychopathology in terms of demographics. We developed a COVID-19 Psychological Response Questionnaire (CPRQ). Further, we estimated the factor structure and internal consistency of CPRQ. Patient Health Questionnaire–9 (PHQ-9) was utilized to assess Major Depressive Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The outbreak of COVID-19 has caused the world to face a major health and safety crisis. The epidemic not only threatens people's physical health, causing various physical symptoms, sequelae, and even death (Lang et al, 2020 ; Odone et al, 2020 ; Speth et al, 2020 ); it also has a huge impact on individual mental health, such as anxiety and depression (Aboul-ata & Qonsua, 2022 ; Chen et al, 2021 ; Choi et al, 2020 ; Yue et al, 2020 ). This is not only because of the epidemic itself, but also because of the overwhelming information given during the epidemic (Catedrilla et al, 2020 ; Gallotti et al, 2020 ; Patel et al, 2020 ; Patwa et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The outbreak of COVID-19 has caused the world to face a major health and safety crisis. The epidemic not only threatens people's physical health, causing various physical symptoms, sequelae, and even death (Lang et al, 2020 ; Odone et al, 2020 ; Speth et al, 2020 ); it also has a huge impact on individual mental health, such as anxiety and depression (Aboul-ata & Qonsua, 2022 ; Chen et al, 2021 ; Choi et al, 2020 ; Yue et al, 2020 ). This is not only because of the epidemic itself, but also because of the overwhelming information given during the epidemic (Catedrilla et al, 2020 ; Gallotti et al, 2020 ; Patel et al, 2020 ; Patwa et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the findings of this study, participants who reported experiencing one mental health-related symptom were more likely to be from the lower socio-economic group. Recent evidence indicated higher socio-economic status to be associated with less likelihood of developing mental healthrelated morbidities (19). Other studies from LMIC contexts have presented similar findings (14,(56)(57)(58).…”
Section: Discussionmentioning
confidence: 61%
“…as the social and economic fallout-all potentially stimulate sadness, anxiety, worry, depression (19), fear (20), anger, frustration, loneliness and stress (9,19,21) during the pandemic.…”
mentioning
confidence: 99%
“…Moreover, most women wear face masks correctly (Ganczak et al, 2021 ) and do not reuse surgical masks (Pereira-Ávila et al, 2020 ). The study on Egyptian women found they had the highest values on anxiousness, avoiding, and cleaning (Aboul-ata and Qonsua, 2022 ). Further study should explore broader on individual face mask perceptions and wearing as well as the role of gender in the relations.…”
Section: Discussionmentioning
confidence: 99%